Case report: Exome sequencing revealed disease-causing variants in a patient with spondylospinal thoracic dysostosis - Bouchoucha, Sami; Chikhaoui, Asma; Najjar, Dorra; Zayoud, Khouloud; Zouari, Mohamed; Nessib, Mohamed Nabil; Kéfi, Rym; Yacoub-Youssef, Houda (Frontiers in Pediatrics, 2023)
Background: Spondylocostal dysostosis is a rare genetic disorder caused by mutations in DLL3, MESP2, LFNG, HES7, TBX6, RIPPLY2. A particular form of this disorder characterized by the association of spondylocostal dysostosis with multiple pterygia has been reported and called spondylospinal thoracic dysostosis. Both disorders affect the spine and ribs, leading to abnormal development of the spine. Spondylospinal thoracic dysostosis is a rare syndrome characterized by the association of multiple vertebral segmentation defects, thoracic cage deformity, and multiple pterygia. This syndrome can be considered as a different form of the described spondylocostal dysostosis. However, no genetic testing has been conducted for this rare disorder so far.Methods: We report here the case of an 18-month-old female patient presenting the clinical and radiological features of spondylospinal thoracic dysostosis. To determine the underlying genetic etiology, whole exome sequencing and Sanger sequencing were performed.Results: Using Whole Exome Sequencing (WES), we identified a variant in TPM2 gene c. 628C>T, already reported in the non-lethal form of multiple pterygium syndrome. Besides, following the analysis of WES data, using bioinformatic tools, for oligogenic diseases, we identified candidate modifier genes, CAP2 and ADCY6, that could impact the clinical manifestations.Conclusion: We showed a potential association between TPM2 and the uncommon spondylocostal dysostosis phenotype that would require further validation on larger cohort.